Some biological notes on the Tawny-breasted Parrotfinch Erythrura hyperythra - Bas van Balen (KUKILA, 1987)
The Tawny-breasted Parrofinch Erythrura hyperythra was described for the first time by Reichenbach in 1862 from a specimen erroneously thought to have been collected in New Guinea. Vordeman (1883) described a second specimen collected in west Java. The parrotfinch has since been reported from Bast Java, Lombok, Sumbawa, Flores, Sulawesi, West and East Malaysia, Luzon and Mindoro. However, because of its rarity and secretive behaviour, very little is known of the bird in nature (but see Burkard, 1982).